Sleep Complaints Affecting School Performance at Different Educational Levels - Pagel, James F.; Kwiatkowski, Carol F. (Frontiers in Neurology, 2010)
The clear association between reports of sleep disturbance and poor school performance has been documented for sleepy adolescents. This study extends that research to students outside the adolescent age grouping in an associated school setting (98 middle school students, 67 high school students, and 64 college students). Reported restless legs and periodic limb movements are significantly associated with lower GPA’s in junior high students. Consistent with previous studies, daytime sleepiness was the sleep variable most likely to negatively affects high school students. Sleep onset and maintenance insomnia were the reported sleep variables significantly correlated with poorer school performance in college students. This study indicates that different sleep disorder variables negatively affect performance at different age and educational levels.